Superabsorbent hydrogel and its preparation method and application
By using spacer cross-linking agents to cross-link polysaccharides, a well-defined polymer network is formed, which solves the problems of difficult structure control and poor mechanical strength caused by random cross-linking of polymer chains in existing SAPs, and achieves higher water absorption. properties and mechanical strength, and reduces costs.
Patent Information
- Application Number
- CN202310059588.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-03-23
- Filing Date
- 2022-03-23
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2042-03-23
AI Technical Summary
The random crosslinking of existing superabsorbent polymer hydrogels (SAPs) in polymer chains results in difficult control of polymer network structure, poor mechanical strength and water absorption, and conventional SAPs lack biodegradability.
Using spacer cross-linkers, a more stable and predictable polymer network is formed by cross-linking moieties containing at least two carboxylic acid groups with the polysaccharide. The structure of the spacer cross-linker is well-defined prior to cross-linking, allowing a more flexible cross-linking pattern to form a looser but high-strength polymer network.
Achieve more controllable water absorption and mechanical strength of polymers and hydrogels, improve the swelling ratio of hydrogels, and reduce the use of cross-linking agents and costs due to the use of long-spaced cross-linking agents, While maintaining a strong polymer network structure.
Smart Images

Figure CN116003830B_ABST
Abstract
Description
[0001] This application is a divisional application with an application date of March 23, 2022, application number 202280002509.2, and invention name “Superabsorbent Hydrogel”. Technical Field
[0002] The invention relates to a hydrogel, in particular to a superabsorbent hydrogel and a preparation method and application thereof. Background Art
[0003] Hydrogels are networks of cross-linked polymer chains that are hydrophilic and capable of absorbing aqueous solutions by hydrogen bonding with water molecules. The water molecules are retained within the hydrogel, causing the hydrogel to swell to many times its initial volume in the process. The structural integrity of the hydrogel network is maintained in water because the cross-linking holds the hydrophilic polymer chains together to form a three-dimensional solid. Superabsorbent polymer hydrogels (SAPs) are hydrogels that can absorb and retain extremely large amounts of liquid relative to their own mass. In deionized and distilled water, SAPs can absorb 300 times their weight (30 to 60 times their own volume) and can become up to 99.9% liquid.
[0004] The overall absorbency and swelling capacity of the hydrogel are controlled by controlling the type and degree of crosslinking agent used to prepare the hydrogel. For example, low-density crosslinked SAPs generally have higher absorbency and swell to a greater extent, resulting in softer and more viscous hydrogel formation. In contrast, SAPs with high crosslinking density exhibit lower absorbency and swelling, but higher gel strength and can maintain their particle shape even under moderate pressure.
[0005] However, in either case, the polymer chains in known SAPs are randomly cross-linked, with little control over the structure of the resulting polymer network, and therefore the properties of the polymer are not easily predictable. In addition, conventional SAPs use short cross-linking agents, resulting in a dense and less flexible polymer network, which in turn results in reduced mechanical strength and water absorption of the polymer and hydrogel. In addition, commercially available conventional SAPs are almost all acrylic products, which lack biodegradability.
[0006] Therefore, there is a need to provide polymers or hydrogels that overcome or at least ameliorate one or more of the above-mentioned disadvantages. Summary of the invention
[0007] In one aspect, a polymer comprising a polysaccharide cross-linked with a spacer cross-linker is provided, wherein the spacer cross-linker comprises a first optionally substituted aliphatic moiety terminated at each end with a second moiety comprising at least two carboxylic acid groups.
[0008] In another aspect, there is provided a hydrogel comprising a polymer as defined above and a liquid.
[0009] Advantageously, the polymer or hydrogel as defined above is cross-linked with a spacer cross-linker, which generally forms a more stable and rigid network than a polymer or hydrogel associated only by non-chemical physical interactions. In addition, in contrast to known polymers and hydrogels in which the spacer groups are randomly cross-linked with the polysaccharide, the polymers of the present application use preformed, well-defined spacer cross-linkers. Therefore, the structure of the spacer cross-linker (including chain length and molecular weight) is well-defined before cross-linking with the polysaccharide, so the resulting polymer is more predictably formed and easier to characterize. Advantageously, the polymer and hydrogel as defined above facilitate a more controllable adjustment of the water absorption of the polymer and hydrogel, resulting in better performance in terms of mechanical strength and medium uptake rate compared to previously known randomly cross-linked hydrogels.
[0010] In another example, the first optionally substituted aliphatic molecule has a molecular weight in the range of about 0.1 kDa to about 100 kDa.
[0011] Advantageously, by using long-spaced crosslinkers, crosslinking between polysaccharide chains can occur in a more flexible and diverse manner, resulting in a polymer with a looser polymer network while still having a high level of strength. A looser polymer network also advantageously promotes a larger swelling ratio of the hydrogel because it allows the polysaccharide chains within the network to move further away from each other, thereby allowing the polymer network to swell to a greater extent.
[0012] In another aspect, there is provided a method of forming a polymer as defined above, the method comprising the steps of:
[0013] a) reacting a first optionally substituted aliphatic molecule comprising at least two hydroxyl groups with a second molecule comprising at least three carboxylic acid groups to form a spacer crosslinker; and
[0014] b) cross-linking the spacer cross-linking agent with the polysaccharide to form a polymer as defined above.
[0015] Advantageously, the method allows the formation of spacer crosslinkers and polymers with or without the use of a catalyst. Advantageously, the reaction can be carried out in the absence of a catalyst, which eliminates the problem of lower yields due to the presence of residual catalyst or the need to remove residual catalyst. Further advantageously, since the structure of the crosslinker is known, there can be better control over the amount of crosslinker used in the reaction.
[0016] More advantageously, due to the long length of the spacer crosslinker, crosslinking within the same polysaccharide chain or multiple crosslinking between the same two polysaccharide chains is unlikely to occur. Therefore, the amount of crosslinker used in the reaction can be reduced while still maintaining a strong polymer network structure, which is an economic advantage.
[0017] In another aspect, there is provided a composition comprising a polymer as defined above or a hydrogel as defined above and a pharmaceutically acceptable excipient.
[0018] In another aspect, there is provided a capsule comprising a polymer as defined above or a hydrogel as defined above.
[0019] In another aspect, there is provided a method for treating obesity, prediabetes, diabetes, non-alcoholic fatty liver disease (NAFLD) or chronic idiopathic constipation or reducing caloric intake or improving glycemic control in a subject in need thereof, the method comprising the step of orally administering to the subject a therapeutically effective amount of a polymer as defined above, or a hydrogel as defined above, or a composition as defined above.
[0020] In another aspect, there is provided a polymer as defined above or a hydrogel as defined above or a composition as defined above for use in treating obesity, prediabetes, diabetes, non-alcoholic fatty liver disease (NAFLD) or chronic idiopathic constipation, or for reducing caloric intake or improving glycemic control.
[0021] In another aspect, there is provided a use of a polymer as defined above, or a hydrogel as defined above, or a composition as defined above, in the preparation of a medicament for treating obesity, prediabetes, diabetes, non-alcoholic fatty liver disease (NAFLD) or chronic idiopathic constipation, or for reducing caloric intake or improving glycemic control.
[0022] Advantageously, the excellent mechanical strength and medium uptake rate of the polymer or hydrogel as defined above can be useful in administering to a patient so that the hydrogel swells in the stomach and reduces caloric intake, improves blood sugar control or improves bowel movements, thereby treating obesity, diabetes, non-alcoholic fatty liver disease (NAFLD) or chronic idiopathic constipation.
[0023] In another aspect, there is provided a method of reducing weight or improving body shape in a healthy subject, the method comprising the step of orally administering to the subject a polymer as defined above, a hydrogel as defined above or a composition as defined above.
[0024] Advantageously, the polymer or hydrogel or composition as defined above may also promote non-medical cosmetic weight loss to improve the body shape of healthy subjects.
[0025] definition
[0026] As used herein, the following words and terms shall have the indicated meanings:
[0027] Unless otherwise indicated, "alkyl" as a group or as part of a group refers to a straight or branched aliphatic hydrocarbon group, preferably a C1-C6 alkyl group. Examples of suitable straight and branched C1-C6 alkyl substituents include methyl, ethyl, n-propyl, 2-propyl, n-butyl, sec-butyl, tert-butyl, hexyl, etc. The group may be a terminal group or a bridging group.
[0028] "Alkoxy" refers to an alkyl group as defined herein, singly bonded to an oxygen group. The group may be a terminal group or a bridging group. If the group is a terminal group, it is bonded to the rest of the molecule through the alkyl group.
[0029] "Heteroalkyl" refers to a straight or branched chain alkyl group preferably having 2 to 6 carbons in the chain, one or more of which has been replaced by a heteroatom selected from S, O, P and N. Exemplary heteroalkyl groups include alkyl ethers, secondary and tertiary alkylamines, amides, thioethers, and the like. Examples of heteroalkyl groups also include hydroxy C1-C6 alkyl, C1-C6 alkoxy C1-C6 alkyl, amino C1-C6 alkyl, C1-C6 alkylamino C1-C6 alkyl, and di(C1-C6 alkyl)amino C1-C6 alkyl. The group may be a terminal group or a bridging group.
[0030] "Heterocycloalkyl" refers to a saturated monocyclic, bicyclic or polycyclic ring containing at least one heteroatom (preferably 1 to 3 heteroatoms) selected from nitrogen, sulfur and oxygen in at least one ring. Each ring is preferably 3 to 10 members, more preferably 4 to 7 members. Examples of suitable heterocycloalkyl substituents include pyrrolidinyl, tetrahydrofuranyl, tetrahydrothiofuranyl, piperidinyl, piperazinyl, tetrahydropyranyl, morpholinyl, 1,3-diazepane, 1,4-diazepane, 1,4-oxazepane and 1,4-oxathipane. Heterocycloalkyl is generally C1-C 12 Heterocycloalkyl. The heterocycloalkyl may contain 3 to 8 ring atoms. The heterocycloalkyl may contain 1 to 3 heteroatoms independently selected from N, O and S. The group may be a terminal group or a bridging group.
[0031] As used herein, the term "optionally substituted" means that the group to which the term refers may be unsubstituted or may be substituted with one or more groups independently selected from the group consisting of acyl, alkyl, alkenyl, alkynyl, thioalkyl, cycloalkyl, cycloalkylalkyl, cycloalkenyl, cycloalkylalkenyl, heterocycloalkyl, cycloalkylheteroalkyl, cycloalkyloxy, cycloalkenyloxy, cycloamino, halogen, carboxyl, haloalkyl, haloalkynyl, alkynyloxy, heteroalkyl, heteroalkenyl, heteroalkynyl, heteroalkoxy, hydroxy, hydroxyalkyl, alkoxy, thioalkoxy, alkenyloxy, haloalkoxy, haloalkenyl, haloalkynyl, haloalkenyloxy, nitro, amino, nitroalkyl, nitroalkenyl, nitroalkynyl, nitroheterocyclyl, alkylamino, dialkylamino, alkenylamine, aminoalkyl, alkynylamino, acyl, alkoxy, alkoxyalkyl, alkoxyaryl, alkoxycarbonyl, alkoxycycloalkyl, alkoxyheteroaryl, alkoxyheterocycloalkyl, alkenoyl, alkynyl Acyl, acylamino, diacylamino, acyloxy, alkylsulfonyloxy, heterocyclyl, heterocyclalkenyl, heterocyclylalkyl, heterocyclylalkylalkyl, heterocyclylalkylalkenyl, heterocyclylalkylalkenyl, heterocyclylheteroalkyl, heterocyclylalkyloxy, heterocyclylalkenyloxy, heterocyclyloxy, heterocyclylamino, halogenated heterocyclylalkyl, alkylsulfinyl, alkylsulfonyl, alkylsulfenyl, alkylcarbonyloxy, alkylthio, acylthio, aminosulfonyl, phosphorus-containing groups such as phosphonyl and phosphinyl, sulfinyl , sulfinylamino, sulfonyl, sulfonylamino, aryl, arylalkyl, arylalkoxy, arylamino, arylheteroalkyl, heteroaryl, heteroarylalkyl, heteroarylalkenyl, heteroarylalkynyl, heteroarylheteroalkyl, heteroarylamino, heteroaryloxy, arylalkenyl, arylalkyl, alkylaryl, alkylheteroaryl, aryloxy, arylsulfonyl, cyano, cyanate, isocyanate, -C(O)NH(alkyl) and -C(O)N(alkyl)2.
[0032] The word "substantially" does not exclude "completely", for example a composition "substantially free of" Y may be completely free of Y. Where necessary, the word "substantially" may be omitted from the definition of the present invention.
[0033] Unless otherwise indicated, the terms "comprising" and "comprise" and their grammatical variations are intended to represent "open" or "inclusive" language such that they include the listed elements and permit the inclusion of additional, unrecited elements.
[0034] As used herein, in the context of formulation component concentrations, the term "about" typically means + / - 5% of the stated value, more typically means + / - 4% of the stated value, more typically means + / - 3% of the stated value, more typically means + / - 2% of the stated value, even more typically means + / - 1% of the stated value, and even more typically means + / - 0.5% of the stated value.
[0035] Throughout the disclosure, certain embodiments may be disclosed in the form of ranges. It should be understood that the description of ranges is only for convenience and brevity, and should not be interpreted as an unchangeable limitation on the scope of the disclosed range. Therefore, the description of a range should be considered to specifically disclose all possible subranges and single numerical values within the range. For example, a description of a range such as 1 to 6 should be considered to specifically disclose subranges such as 1 to 3, 1 to 4, 1 to 5, 2 to 4, 2 to 6, 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6. This applies regardless of the width of the range.
[0036] Certain embodiments may also be described broadly and generally herein. Each of the narrower classes and subclass groupings falling within the general disclosure also form part of the present disclosure. This includes a general description of the embodiments with a proviso or negative limitation removing any subject matter from the class, regardless of whether the removed material is specifically recited herein. DETAILED DESCRIPTION
[0037] A polymer comprising a polysaccharide cross-linked with a spacer cross-linker is provided, wherein the spacer cross-linker comprises a first optionally substituted aliphatic moiety terminated at each end with a second moiety comprising at least two carboxylic acid groups.
[0038] Hydrogel is obtained by physical or chemical stabilization of polymer fiber aqueous solution. Physical stabilization can be achieved via hydrogen bonding, hydrophobic interactions and chain entanglement. These interactions are usually reversible, and therefore, the hydrogel produced by the polymer mainly comprising physical interactions can easily flow or degrade. In contrast, chemical crosslinking is composed of covalent chemical bonds, and the hydrogel formed using the polymer (as defined above) comprising chemical crosslinking usually forms a more stable and rigid network. The crosslinking degree and type of the crosslinking agent used affect the physical properties of the resulting hydrogel, such as water retention, mechanical strength and degradation rate.
[0039] The spacer crosslinker may have the following formula (I):
[0040] ALZLA(I)
[0041] in
[0042] Z is a first optionally substituted aliphatic moiety;
[0043] A is a second moiety comprising at least two carboxylic acid groups; and
[0044] L is a linking group.
[0045] The first optionally substituted aliphatic moiety or Z can be derived from a first optionally substituted aliphatic molecule comprising at least two hydroxyl groups. In this context, "derived" means that the first optionally substituted aliphatic moiety is formed as a result of the following reaction: at least two hydroxyl groups of the first optionally substituted aliphatic molecule react with a second molecule as further defined below to form a part of the linking group L in formula (I).
[0046] The first optionally substituted aliphatic molecule may be a linear molecule and terminated at each end with a hydroxyl group.
[0047] The first optionally substituted aliphatic molecule can have a molecular weight of about 0.1 kDa to about 100 kDa, about 0.1 kDa to about 0.2 kDa, about 0.1 kDa to about 0.5 kDa, about 0.1 kDa to about 1 kDa, about 0.1 kDa to about 2 kDa, about 0.1 kDa to about 5 kDa, about 0.1 kDa to about 10 kDa, about 0.1 kDa to about 20 kDa, about 0.1 kDa to about 50 kDa, about 0.2 kDa to about 0.5 kDa, about 0.1 kDa to about 10 ... about 0.2 kDa to about 1 kDa, about 0.2 kDa to about 2 kDa, about 0.2 kDa to about 5 kDa, about 0.2 kDa to about 10 kDa, about 0.2 kDa to about 20 kDa, about 0.2 kDa to about 50 kDa, about 0.2 kDa to about 100 kDa, about 0.5 kDa to about 1 kDa, about 0.5 kDa to about 2 kDa, about 0.5 kDa to about 5 kDa, about 0.5 kDa to about 10 kDa, about 0.5 kDa to about kDa to about 20 kDa, about 0.5 kDa to about 50 kDa, about 0.5 kDa to about 100 kDa, about 1 kDa to about 2 kDa, about 1 kDa to about 5 kDa, about 1 kDa to about 10 kDa, about 1 kDa to about 20 kDa, about 1 kDa to about 50 kDa, about 1 kDa to about 100 kDa, about 2 kDa to about 5 kDa, about 2 kDa to about 10 kDa, about 2 kDa to about 20 kDa, about 2 kDa to about 50 kDa, about 2 kDa to about 100 kDa, about 5 kDa to about 10 kDa, about 5 kDa to about 20 kDa, about 5 kDa to about 50 kDa, about 5 kDa to about 100 kDa, about 10 kDa to about 20 kDa, about 10 kDa to about 50 kDa, about 10 kDa to about 100 kDa, about 20 kDa to about 50 kDa, about 20 kDa to about 100 kDa, or about 50 kDa to about 100 kDa.
[0048] The use of long hydrophilic spacer crosslinkers (such as spacer crosslinkers having a molecular weight as defined above) allows the formation of polymers with loose polymer networks while still achieving high levels of strength as measured by swollen state tensile modulus. A looser polymer network results in a hydrogel having a larger swelling ratio because it allows the polysaccharide chains within the network to move further away from each other, thereby allowing the polymer network to swell to a greater extent.
[0049] When using short cross-linking agents such as citric acid, two polysaccharide chains can be connected at a certain distance via a third polysaccharide chain connecting these two chains. However, the length of the linking group is random. Therefore, usually, the length of the linking group determines the proximity of the connected polysaccharide chains. Since multiple cross-linking agents can be connected to a single chain at a random point, the use of short cross-linking agents leads to a polymer network in which the polysaccharide chains are closely connected, thereby leading to a dense network. In contrast, when using long hydrophilic cross-linking agents, the distance between the two polysaccharide chains will be determined by the length of the long hydrophilic cross-linking agent. Since the polysaccharide chains are connected to each other via a fixed chain length corresponding to the length of the long hydrophilic cross-linking agent, the use of long hydrophilic cross-linking agents will lead to a looser polymer network.
[0050] The strength of the hydrogel depends on the degree of interaction between the polymer chains. When using short crosslinkers such as citric acid, due to its short length, once one end of the crosslinker reacts with the polysaccharide chain, the other end can only react within the same polysaccharide chain, or react with another polysaccharide chain in close proximity to the first polysaccharide chain. This severely limits the crosslinked network that can be formed. The mobility of the short crosslinker that reacts with the polysaccharide chain at one end is low because the polysaccharide chain itself is long and relatively fixed. This limited mobility prevents the other end of the crosslinker from moving around, and therefore leads to crosslinking within the same polysaccharide chain, or crosslinking with the second polysaccharide chain that has been crosslinked with the first polysaccharide chain, because they are already in close proximity to each other. This is not ideal because intramolecular crosslinking reduces the swelling ratio without significantly increasing the tensile modulus.
[0051] In contrast, if a long hydrophilic crosslinker is used, due to the flexible nature of the long crosslinker, when one end of the crosslinker reacts with a polysaccharide chain, the other end can move around and react with a polysaccharide chain that is significantly further away from the first polysaccharide chain. Therefore, when a long hydrophilic crosslinker is used, the second polysaccharide chain is most likely to be a different chain that is not crosslinked with the first polysaccharide chain. This overcomes the limitation of low mobility observed when using short crosslinkers. In addition, since crosslinking within the same polysaccharide chain or multiple crosslinking between two polysaccharide chains is less likely to occur, the amount of crosslinker used can be reduced while still maintaining a strong polymeric network structure.
[0052] The first optionally substituted aliphatic molecule may be saturated or unsaturated, straight chain or branched.
[0053] The first optionally substituted aliphatic molecule may comprise an optionally substituted alkyl or an optionally substituted heteroalkyl. The optionally substituted alkyl may be optionally substituted with a substituent selected from hydroxy, alkoxy, carboxyl, thioalkoxy and carboxamide. The optionally substituted heteroalkyl may be ether or amine.
[0054] The first optionally substituted aliphatic molecule may be a hydrophilic polymer.
[0055] The first optionally substituted aliphatic molecule may be selected from polyethers, polyacrylamides, polyethyleneimines, polyacrylates, polymethacrylates, polyvinylpyrrolidones and polyvinyl alcohols, each of which further comprises at least two hydroxyl groups.
[0056] The first optionally substituted aliphatic moiety or Z may have the structure: in
[0057] Q is -CH2-, -O- or -NH2-,
[0058] R is hydrogen, -OH, optionally substituted C1 to C6 alkyl, -C(O)OM, -C(O)NR 2 R 3 or optionally substituted heterocycloalkyl,
[0059] R 2 and R 3 are independently hydrogen or optionally substituted C1 to C6 alkyl,
[0060] M is R 2 , Na or K,
[0061] p is an integer ranging from 1 to 6,
[0062] n is an integer in the range of 2 to 2000, and
[0063] *Indicates the position where this moiety is attached to the rest of the spacer crosslinker.
[0064] R may be hydrogen, methyl, ethyl, propyl, butyl, pentyl or hexyl. R may be hydrogen or methyl.
[0065] R may be -C(O)OH, -C(O)ONa or -C(O)OK.
[0066] The heteroatom of the optionally substituted heterocycloalkyl group may be N.
[0067] The optionally substituted heterocycloalkyl group may contain a heteroatom N and may be bonded to the remainder of the optionally substituted aliphatic moiety via this N atom.
[0068] R may be selected from 2-pyrrolidone, 3-pyrrolidone, pyrrolidine, imidazolidine, pyrazolidine, piperidine, morpholine and dioxazine.
[0069] R can be C(O)NR 2 R 3 , and when R is C(O)NR 2 R 3 When R 2 and R 3 Both may be hydrogen.
[0070] p can be an integer of 1, 2, 3, 4, 5 or 6.
[0071] n may be 2 to 5, 2 to 10, 2 to 20, 2 to 50, 20 to 100, 2 to 200, 2 to 500, 2 to 1000, 2 to 2000, 5 to 10, 5 to 20, 5 to 50, 5 to 100, 5 to 200, 5 to 500, 5 to 1000, 5 to 2000, 10 to 20, 10 to 50, 10 to 100, 10 to 200, 10 to 500, 10 to 1000, 10 to 2000, 20 to 50, 20 to 10 or an integer in the range of 0, 20 to 200, 20 to 500, 20 to 1000, 20 to 2000, 50 to 100, 50 to 200, 50 to 500, 50 to 1000, 50 to 2000, 100 to 200, 100 to 500, 100 to 1000, 100 to 2000, 200 to 500, 200 to 1000, 200 to 2000, 500 to 1000, 500 to 2000, or 1000 to 2000.
[0072] The first optionally substituted aliphatic moiety or Z may have the structure: in
[0073] R is hydrogen or an optionally substituted C1 to C6 alkyl group,
[0074] n is an integer in the range of 2 to 2000, and
[0075] *Indicates the position where this moiety is attached to the rest of the spacer crosslinker.
[0076] The first optionally substituted aliphatic molecule may be polyethylene glycol or polypropylene glycol, each further comprising at least two hydroxyl groups.
[0077] Polyethylene glycol (PEG) is an amphiphilic polyether soluble in water and many organic solvents. PEG is readily available in a wide range of molecular weights, has been found to be non-toxic and approved by the US Food and Drug Administration (FDA). Modified PEGs with low polydispersity index and reactive groups at both ends can be used as long hydrophilic cross-linkers to prepare hydrogels with different physical properties, depending on the PEG chain length used.
[0078] The second part or A comprising at least two carboxylic acid groups can be derived from a second molecule having at least three carboxylic acid groups. In this context, "derived" means that the second part comprising at least two carboxylic acid groups is formed when one of the carboxylic acid groups of the second molecule having at least three carboxylic acid groups reacts to form a part of the linking group L in formula (I).
[0079] Two of the at least two carboxylic acid groups in the second moiety or A may be separated by 2 to 6 atoms, 2 to 3 atoms, 2 to 4 atoms, 2 to 5 atoms, 3 to 4 atoms, 3 to 5 atoms, 3 to 6 atoms, 4 to 5 atoms, 4 to 6 atoms, or 5 to 6 atoms. Advantageously, by having two of the at least two carboxylic acid groups separated by 2 to 6 atoms, the second moiety or A may form a cyclic anhydride intermediate that may act as an intramolecular catalyst during the crosslinking process between the spacer crosslinker and the polysaccharide.
[0080] The second molecule having at least three carboxylic acid groups may be selected from citric acid, pyromellitic acid, butanetetracarboxylic acid and benzoquinonetetracarboxylic acid.
[0081] The second moiety or A comprising at least two carboxylic acid groups may be selected from:
[0082]
[0083] where * indicates the position where this moiety is attached to the rest of the spacer cross-linker.
[0084] L may be independently selected from amides, esters, anhydrides and thioesters.
[0085] The polysaccharide may be selected from starch, cellulose, galactomannan and alginate.
[0086] In view of the growing concern for environmental protection, recent interest has been devoted to the development of superabsorbent hydrogels based on biodegradable materials, which have properties similar to those of traditional, but non-biodegradable, superabsorbent polyacrylates. Suitable biodegradable polymers include polysaccharides, such as alginates, starches and cellulose derivatives.
[0087] The polysaccharide may contain at least one carboxymethyl group.
[0088] The polysaccharide may be carboxymethyl cellulose.
[0089] Carboxymethylcellulose (CMC) or cellulose gum is a cellulose derivative having carboxymethyl groups (-CH2-COOH) bound to some of the hydroxyl groups of the pyranose glucose monomers that make up the cellulose backbone. CMC can be synthesized by the base-catalyzed reaction of cellulose with chloroacetic acid. The reaction is followed by a purification process to produce pure CMC for food, pharmaceutical and dentifrice (toothpaste) applications.
[0090] CMC can be used in food as a viscosity modifier or thickener for stabilizing emulsions in various products including ice cream. It is also a component of many non-food products such as toothpaste, laxatives, diet pills, water-based paints, detergents, fabric sizing agents, reusable heat packs, and various paper products. The main reasons for its use are that it has high viscosity, is non-toxic, and is generally considered hypoallergenic because the main source of the fiber is softwood pulp or cotton linters.
[0091] The carboxymethyl cellulose can have a degree of substitution ranging from about 0.6 to about 1.0, from about 0.6 to about 0.8, or from about 0.8 to about 1.0.
[0092] The functional properties of CMC can depend on the degree of substitution of the cellulose structure, as well as the chain length of the cellulose backbone structure and the degree of aggregation of the carboxymethyl substituents. A degree of substitution ranging from about 0.6 to about 1.0 allows for better emulsification properties and improved acid and salt resistance.
[0093] The viscosity of the polysaccharide as a 1% (wt / wt) aqueous solution at 25° C. may be greater than about 1000 cps, greater than about 2000 cps, greater than about 3000 cps, greater than about 5000 cps, greater than about 7000 cps, or greater than about 10,000 cps. The viscosity of the polysaccharide as a 1% (wt / wt) aqueous solution at 25° C. may be in the range of about 1000 cps to about 12000 cps, about 1000 cps to about 5000 cps, about 1000 cps to about 10,000 cps, about 5000 cps to about 10,000 cps, about 5,000 cps to about 12,000 cps, or about 10,000 cps to about 12,000 cps.
[0094] The polysaccharide molecular weight may have a polydispersity index of less than 10, less than 5, or less than 2. The polysaccharide may have a polydispersity index in the range of about 1 to about 10.
[0095] The polymer may be in the form of a powder having a particle size ranging from about 0.05 mm to about 5 mm, from about 0.05 mm to about 0.1 mm, from about 0.05 mm to about 2 mm, from about 0.1 mm to about 0.2 mm, from about 0.1 mm to about 0.5 mm, from about 0.1 mm to about 1 mm, from about 0.1 mm to about 2 mm, from about 0.1 mm to about 5 mm, from about 0.2 mm to about 0.5 mm, from about 0.2 mm to about 0.5 mm, from about 0.2 mm to about 1 mm, from about 0.2 mm to about 2 mm, from about 0.2 mm to about 5 mm, from about 0.5 mm to about 1 mm, from about 0.5 mm to about 2 mm, from about 0.5 mm to about 5 mm,
[0096] The polymer as defined above may be biodegradable. The polymer as defined above may comprise carboxymethylcellulose as a polysaccharide, a first optionally substituted aliphatic moiety derived from polyethylene glycol terminated with hydroxyl groups at each end, and a second moiety derived from citric acid. Each of the carboxymethylcellulose, polyethylene glycol and citric acid may be independently biodegradable, so the resulting polymer is also biodegradable.
[0097] Also provided is a hydrogel comprising a polymer as defined above and a liquid.
[0098] The liquid may be an aqueous liquid. The liquid may be water, a buffer, gastric fluid, simulated gastric fluid, or any mixture thereof.
[0099] The hydrogel may have rheological properties measured by a G' value ranging from about 500 Pa to about 10,000 Pa, from about 500 Pa to about 1000 Pa, from 500 Pa to about 2000 Pa, from about 500 Pa to about 5000 Pa, from about 1000 Pa to about 2000 Pa, from about 1000 Pa to about 5000 Pa, from about 1000 Pa to about 10,000 Pa, from about 2000 Pa to about 5000 Pa, from about 1000 Pa to about 10,000 Pa, from about 2000 Pa to about 5000 Pa, from about 2000 Pa to about 10,000 Pa, or from about 5000 Pa to about 10,000 Pa.
[0100] The hydrogel may have a media uptake ratio (MUR) of at least 50, at least 70, at least 90, or at least 100. The hydrogel may have a media uptake ratio in the range of about 50 to about 200.
[0101] At least about 70%, about 80%, or about 90%, or 100% by mass of the hydrogel may comprise the polymer in the form of particles ranging in size from about 0.1 mm to about 2 mm.
[0102] The hydrogel can have a tape density ranging from about 0.2 g / mL to about 2.0 g / mL, about 0.2 g / mL to about 0.5 g / mL, about 0.2 g / mL to about 1.0 g / mL, about 0.5 g / mL to about 1.0 g / mL, about 0.5 g / mL to about 2.0 g / mL, or about 1.0 g / mL to about 2.0 g / mL.
[0103] The hydrogel may have a loss on drying of about 20% (wt / wt) or less, about 10% (wt / wt) or less, about 5% (wt / wt) or less, about 2% (wt / wt) or less, or about 1% (wt / wt) or less. The hydrogel may have a loss on drying in the range of about 0.1% (wt / wt) to about 20% (wt / wt).
[0104] The hydrogel may have a G' value in the range of about 500 Pa to 10,000 Pa and a media uptake of at least 50 when measured on a polymer sample in particle form, wherein at least 80% by mass of the particles are in the size range of 0.1 mm to 2 mm, a tape density in the range of 0.5 g / mL to 1.0 g / mL, and a loss on drying of 10% (wt / wt) or less.
[0105] There is also provided a method of forming a polymer as defined above, the method comprising the steps of:
[0106] a) reacting a first optionally substituted aliphatic molecule comprising at least two hydroxyl groups with a second molecule comprising at least three carboxylic acid groups to form a spacer crosslinker; and
[0107] b) cross-linking the spacer cross-linking agent with the polysaccharide to form a polymer as defined above.
[0108] Reaction step (a) may also comprise a polymer additive.
[0109] The polymer additive may be a hydrophilic molecule that may be added to the mixture of the first optionally substituted aliphatic molecule comprising at least two hydroxyl groups and the second molecule comprising at least three carboxylic acid groups prior to the crosslinking step to form a spacer crosslinker to impart additional properties to the polymer or hydrogel, such as increasing the rate at which the resulting polymer or hydrogel swells. The polymer additive may be at least partially crosslinked with the polymer. The polymer additive may not be substantially crosslinked with the polymer. The polymer additive may not be crosslinked with the polymer.
[0110] The polymer may comprise a polysaccharide as defined above crosslinked with a spacer crosslinker as defined above and at least partially crosslinked with a polymer additive as defined above.
[0111] The polymer may comprise a polysaccharide as defined above cross-linked with a spacer cross-linker as defined above, but the additive as defined above may not be cross-linked with the polymer.
[0112] The polymer additive may be a plasticizer. The polymer additive may be a hydrophilic oligomer such as polyethylene glycol (PEG), etc. Advantageously, PEG may be highly hydrophilic, may hinder entanglement of the spacer crosslinker, and may be easily added to the polymer without affecting the number of reactive hydroxyl groups per unit mass.
[0113] When a crosslinking agent as defined above is used in a crosslinking reaction of a polymer, the crosslinking agents may become entangled with each other, which may limit the mobility of the polymer space network. Polymer additives such as plasticizers and the like can prevent the entanglement of the crosslinking agent during the crosslinking process, thereby ensuring a higher mobility of the polymer space network and thus ensuring a better swelling rate.
[0114] The hydrophilic oligomer may be selected from PEG-100, PEG-200, PEG-400, PEG-1000 and any mixture thereof.
[0115] Reaction step (a) may further comprise a catalyst. The catalyst may be selected from ammonia, ammonium sulfate, aluminum sulfate, magnesium chloride, magnesium acetate, zinc chloride, zinc nitrate and any mixture thereof, or the catalyst may comprise phosphorus. The catalyst may be sodium phosphate, sodium hypophosphite or a mixture by weight (1:1) of sodium bicarbonate and disodium hydrogen phosphate.
[0116] Reaction step (a) may be performed in the absence of a catalyst.
[0117] The reacting step (a) and the cross-linking step (b) can be independently performed at a temperature ranging from about 80°C to about 180°C, about 80°C to about 100°C, about 80°C to about 130°C, about 80°C to about 150°C, about 100°C to about 130°C, about 100°C to about 150°C, about 100°C to about 180°C, about 130°C to about 150°C, about 130°C to about 180°C, or about 150°C to about 180°C.
[0118] During the cross-linking step (b), the weight ratio of the second molecule comprising at least three carboxylic acid groups to the polysaccharide may be less than about 1:30, less than about 1:50, less than about 1:100, less than about 1:500. The weight ratio of the second molecule comprising at least three carboxylic acid groups to the polysaccharide may be in the range of about 1:30 to about 1:50, 1:30 to about 1:100, about 1:30 to about 1:500, about 1:30 to about 1:1000, about 1:50 to about 1:100, about 1:50 to about 1:500, about 1:50 to about 1:1000, about 1:100 to about 1:500, about 1:100 to about 1:500, or about 1:500 to about 1:1000.
[0119] The method may further comprise the following steps (a1), (a2) and (a3) between the reaction step (a) and the cross-linking step (b):
[0120] a1) mixing the spacer crosslinking agent and the polysaccharide in a solvent to form a homogenized mixture,
[0121] a2) drying the homogenized mixture at a temperature in the range of about 40° C. to about 90° C. to remove the solvent, and
[0122] a3) grinding the dried homogenized mixture to form a powder having a particle size ranging from about 0.05 mm to about 5 mm.
[0123] The mixing step a1) may also comprise polymer additives as defined above.
[0124] The step of drying the homogenized mixture may be performed at a temperature ranging from about 40°C to about 90°C, from about 40°C to about 60°C, or from about 60°C to about 90°C.
[0125] The powder of the dried homogenized mixture may have a particle size ranging from about 0.05 mm to about 5 mm, about 0.05 mm to about 0.1 mm, about 0.05 mm to about 2 mm, about 0.1 mm to about 0.2 mm, about 0.1 mm to about 0.5 mm, about 0.1 mm to about 1 mm, about 0.1 mm to about 2 mm, about 0.1 mm to about 5 mm, about 0.2 mm to about 0.5 mm, about 0.2 mm to about 0.5 mm, about 0.2 mm to about 1 mm, about 0.2 mm to about 2 mm, about 0.2 mm to about 5 mm, about 0.5 mm to about 1 mm, about 0.5 mm to about 2 mm, about 0.5 mm to about 5 mm, about 0.5 mm to about 1 mm, about 0.5 mm to about 2 mm, about 0.5 mm to about 5 mm, about 1 mm to about 2 mm, about 1 mm to about 5 mm, or about 2 mm to about 5 mm.
[0126] The method may further include the step of washing the polymer with deionized water after the crosslinking step (b). The polymer washing step may be performed for a time ranging from about 2 hours to about 36 hours, about 2 hours to about 6 hours, about 2 hours to about 12 hours, about 2 hours to about 18 hours, about 2 hours to about 24 hours, about 6 hours to about 12 hours, about 6 hours to about 18 hours, about 6 hours to about 24 hours, about 12 hours to about 18 hours, about 12 hours to about 24 hours, about 12 hours to about 36 hours, about 18 hours to about 24 hours, about 18 hours to about 36 hours, about 24 hours to about 36 hours, or about 24 hours to about 36 hours.
[0127] During the washing step, the washing solution (deionized water) may be changed 1, 2, 3, 4 or 5 times to remove any impurities.
[0128] The method may also include a step of drying the polymer after the washing step. The drying of the polymer may be performed at a temperature in the range of about 40°C to about 90°C, about 40°C to about 60°C, or about 60°C to about 90°C. The drying of the polymer may be performed for a time in the range of about 6 hours to about 36 hours, about 6 hours to about 12 hours, about 6 hours to about 18 hours, about 6 hours to about 24 hours, about 12 hours to about 18 hours, about 12 hours to about 24 hours, about 12 hours to about 36 hours, about 18 hours to about 24 hours, about 18 hours to about 36 hours, or about 24 hours to about 36 hours.
[0129] The method may further include the step of grinding the polymer to form a powder having a particle size ranging from about 0.05 mm to about 5 mm after the step of drying the polymer.
[0130] The method may further comprise the step of adding a liquid to the polymer.
[0131] In the presence of a liquid, a cross-linked polymer can be considered a hydrogel.
[0132] Also provided is a polymer obtainable by a process as defined above.
[0133] There is also provided a hydrogel obtainable by a process as defined above when the polymer is in contact with a liquid.
[0134] Also provided is a composition comprising a polymer as defined above or a hydrogel as defined above and a pharmaceutically acceptable excipient.
[0135] The polymer composition may also comprise polymer additives as defined above.
[0136] The polymer or hydrogel may be administered alone. Alternatively, the polymer or hydrogel may be administered as a pharmaceutical formulation, a veterinary formulation, or an industrial formulation. The polymer or hydrogel may also be present as a suitable salt, including a pharmaceutically acceptable salt.
[0137] The language "pharmaceutically acceptable excipients" is intended to include, but is not limited to, solvents, dispersion media, coatings, antibacterial and antifungal agents, isotonic and absorption delaying agents, and the like. The use of such media and agents for pharmaceutically active substances is well known in the art. Unless any conventional media or agents are incompatible with the polymer or hydrogel, their use in therapeutic compositions and methods of treatment and prevention is contemplated. Supplementary active compounds may also be added.
[0138] It is particularly advantageous to formulate parenteral compositions in unit dosage form for ease of administration and uniformity of dosage. As used herein, "unit dosage form" refers to physically discrete units suitable as unit dosages for individuals to be treated; each unit containing a predetermined amount of polymer or hydrogel is calculated to produce the desired therapeutic effect together with the required pharmaceutical excipients. The polymer or hydrogel can be formulated into acceptable dosage units in effective amounts together with suitable pharmaceutically acceptable excipients for convenient and effective administration. In the case of compositions containing supplementary active ingredients, the dosage is determined by reference to the usual dose and mode of administration of the ingredient.
[0139] Excipients may be selected from, but not limited to, medicaments such as gum tragacanth, gum arabic, corn starch or gelatin, etc.; excipients such as dicalcium phosphate; disintegrants such as corn starch, potato starch, alginic acid, etc.; lubricants such as magnesium stearate; and sweeteners such as sucrose, lactose or saccharin, or flavorings such as peppermint, wintergreen oil or cherry flavorings. When the unit dosage form is a capsule, in addition to the above types of materials, it may also contain a liquid carrier. Various other materials may exist as a coating, or be used to otherwise change the physical form of the dosage unit. For example, tablets, pills or capsules may be coated with shellac, sugar or both. Syrups or elixirs may contain analogs, sucrose as a sweetener, methylparaben and propylparaben as preservatives, dyes and flavorings such as cherry or orange flavorings. Of course, any material used in preparing any unit dosage form should be pharmaceutically pure and substantially non-toxic in the amounts employed. In addition, analogs may be incorporated into sustained-release preparations and formulations.
[0140] In one example, the excipient is an orally administrable excipient.
[0141] Also provided is a capsule comprising a polymer as defined above or a hydrogel as defined above.
[0142] Each capsule may contain the polymer as defined above in an amount ranging from about 0.5g to about 1g, from about 0.5g to about 0.75g or from about 0.75g to about 1g. Each capsule may contain the polymer as defined above in an amount ranging from about 0.7g to about 0.8g.
[0143] Capsules can be made of gelatin and can be used to orally administer the polymer or hydrogel to a subject.
[0144] In one example, the polymer or hydrogel is to be administered orally. The polymer or hydrogel can be administered orally, for example, with an inert diluent or an absorbable edible carrier. The polymer or hydrogel and other ingredients can also be encapsulated in a hard or soft shell gelatin capsule, compressed into tablets, or added directly to the diet of the individual. For oral therapeutic administration, the polymer or hydrogel can be added with excipients and used in the form of ingestible tablets, buccal tablets, lozenges, capsules, elixirs, suspensions, syrups, biscuits, etc.
[0145] Also provided is a method for treating obesity, prediabetes, diabetes, non-alcoholic fatty liver disease (NAFLD) or chronic idiopathic constipation or reducing caloric intake or improving glycemic control in a subject in need thereof, the method comprising the step of orally administering to the subject a therapeutically effective amount of a polymer as defined above, or a hydrogel as defined above, or a composition as defined above.
[0146] As used herein, the term "treat" refers to any and all uses that correct a disease state or symptoms in any way, prevent disease establishment, or prevent, hinder, delay, or reverse the progression of disease or other undesirable symptoms.
[0147] One skilled in the art is able to determine effective, non-toxic dosage levels of the polymer or hydrogel and modes of administration suitable for treating the disease or condition for which the polymer or hydrogel is indicated.
[0148] Additionally, it will be apparent to one of ordinary skill in the art that routine treatment course determination testing can be used to determine the optimal treatment course, such as the number of doses of polymer or hydrogel to be administered per day over a defined number of days.
[0149] The polymer or hydrogel may be administered alone. Alternatively, the polymer or hydrogel may be administered as a pharmaceutical formulation, a veterinary formulation, or an industrial formulation. The polymer or hydrogel may also be present as a suitable salt, including a pharmaceutically acceptable salt.
[0150] In one example, the polymer or hydrogel is to be administered orally. The polymer or hydrogel can be administered orally, for example, with an inert diluent or an absorbable edible carrier. The polymer or hydrogel and other ingredients can also be encapsulated in a hard or soft shell gelatin capsule, compressed into tablets, or added directly to the diet of the individual. For oral therapeutic administration, the polymer or hydrogel can be added with excipients and used in the form of ingestible tablets, buccal tablets, lozenges, capsules, elixirs, suspensions, syrups, biscuits, etc.
[0151] It is particularly advantageous to formulate parenteral compositions in unit dosage form for ease of administration and uniformity of dosage. As used herein, "unit dosage form" refers to physically discrete units suitable as unit dosages for individuals to be treated; each unit containing a predetermined amount of polymer or hydrogel is calculated to produce the desired therapeutic effect together with the required pharmaceutical excipients. The polymer or hydrogel can be formulated into acceptable dosage units in effective amounts together with suitable pharmaceutically acceptable excipients for convenient and effective administration. In the case of polymers or hydrogels containing supplementary active ingredients, the dosage is determined by reference to the usual dose and mode of administration of the ingredient.
[0152] Unit dosage forms can be, for example, in solid form, such as pills, tablets, capsules, lozenges, wafers or crackers, or in liquid form, such as solutions or emulsions.
[0153] The unit dosage form in solid form may be further coated with a pharmaceutically acceptable excipient. Coating of the unit dosage form may be performed in a fluidized bed processor using a bottom spray, top spray, or tangential spray attachment. The flowability, processability, and other characteristics of the unit dosage form may be easily controlled by selecting appropriate pharmaceutically acceptable excipients to be coated on the unit dosage form; and by varying process variables such as spray rate and degree of fluidization.
[0154] In one example, the polymer or hydrogel is administered in a single dose or multiple doses. In one example, the polymer or hydrogel is administered in a single dose, two doses, three doses, or four doses. In another example, the polymer or hydrogel can or will be administered at intervals of, but not limited to, hourly, daily, twice a day, three times a day, four times a day, every two days, every three days, every four days, every five days, every six days, every week, every two weeks, every two months, every month, or a combination thereof.
[0155] Generally, the effective dose per 24 hours can be from about 0.001 mg to about 500 mg / kg body weight; from about 0.001 mg to about 0.01 mg / kg body weight, from about 0.001 mg to about 0.1 mg / kg body weight, from about 0.001 mg to about 1 mg / kg body weight, from about 0.001 mg to about 10 mg / kg body weight, from about 0.001 mg to about 100 mg / kg body weight, from about 0.01 mg to about 500 mg / kg body weight; from about 0.01 mg to about 0.1 mg / kg body weight, from about 0.01 mg to about 1 mg / kg body weight, from about 0.001 mg to about 100 mg / kg body weight, from about 0.01 mg to about 500 mg / kg body weight; 0.01 mg to about 10 mg / kg body weight, about 0.01 mg to about 100 mg / kg body weight, about 0.1 mg to about 500 mg / kg body weight; about 0.1 mg to about 1 mg / kg body weight, about 0.1 mg to about 10 mg / kg body weight, about 0.1 mg to about 100 mg / kg body weight, about 1 mg to about 500 mg / kg body weight; about 1 mg to about 10 mg / kg body weight, about 1 mg to about 100 mg / kg body weight, about 10 mg to about 500 mg / kg body weight; about 10 mg to about 100 mg / kg body weight. More suitably, the effective dose per 24 hours can be in the range of about 10 mg to about 500 mg / kg body weight; about 10 mg to about 250 mg / kg body weight; about 50 mg to about 500 mg / kg body weight; about 50 mg to about 200 mg / kg body weight; or about 50 mg to about 100 mg / kg body weight.
[0156] A typical effective dose may be once a week, twice a week, three times a week, once a day, twice a day, or three times a day.
[0157] A conventional effective dose may be two or three times a day, and each dose may comprise one, two, three, four or five unit dosage forms as defined above.
[0158] Each dose may contain from about 1 g to about 6 g, from about 1 g to about 2 g, from about 1 g to about 3 g, from about 1 g to about 4 g, from about 1 g to about 5 g, from about 2 g to about 3 g, from about 2 g to about 3 g, from about 2 g to about 4 g, from about 2 g to about 5 g, from about 2 g to about 5 g, from about 2 g to about 5 g, from about 2 g to about 6 g, from about 3 g to about 4 g, from about 3 g to about 5 g, from about 3 g to about 6 g, from about 4 g to about 5 g, from about 3 g to about 6 g, from about 4 g to about 5 g, from about 4 g to about 6 g, or from about 5 g to about 6 g of a polymer or hydrogel as defined above.
[0159] Each dose may contain 2 to 8 unit dosage forms, 2 to 3 unit dosage forms, 2 to 4 unit dosage forms, 2 to 5 unit dosage forms, 2 to 6 unit dosage forms, 2 to 7 unit dosage forms, 3 to 4 unit dosage forms, 3 to 5 unit dosage forms, 3 to 6 unit dosage forms, 3 to 7 unit dosage forms, 3 to 8 unit dosage forms, 4 to 5 unit dosage forms, 4 to 6 unit dosage forms, 4 to 7 unit dosage forms, 4 to 8 unit dosage forms, 5 to 6 unit dosage forms, 5 to 7 unit dosage forms, 5 to 8 unit dosage forms, 6 to 7 unit dosage forms, 6 to 8 unit dosage forms or 7 to 8 unit dosage forms, which unit dosage forms contain a polymer or hydrogel as defined above.
[0160] Each dose may contain about 2.24 g of a polymer or hydrogel as defined above, administered in 4 unit dosage forms, wherein each unit dosage form in the form of a capsule may contain about 0.56 g of a polymer or hydrogel as defined above.
[0161] The polymer or hydrogel can be administered before a meal. The polymer or hydrogel can be administered from about 10 minutes to about 1 hour, from about 10 minutes to about 20 minutes, from about 10 minutes to about 30 minutes, from about 10 minutes to about 45 minutes, from about 20 minutes to about 30 minutes, from about 20 minutes to about 45 minutes, from about 20 minutes to about 1 hour, from about 30 minutes to about 45 minutes, from about 30 minutes to about 1 hour, from about 45 minutes to about 1 hour, before a meal.
[0162] The polymer or hydrogel can be administered with water. The polymer or hydrogel can be administered with about 100 mL to about 700 mL, about 100 mL to about 250 mL, about 100 mL to about 500 mL, about 250 mL to about 500 mL, about 250 mL to about 700 mL, or about 500 mL to about 700 mL of water.
[0163] The polymers or hydrogels of the invention may be used in combination with other known treatments for diseases or conditions.Combinations of active agents, including polymers or hydrogels, may be synergistic.
[0164] The subject may be, but is not limited to, an animal at risk of or suffering from obesity, prediabetes, diabetes, non-alcoholic fatty liver disease (NAFLD), or chronic idiopathic constipation. The subject may also need to reduce caloric intake or improve glycemic control. In one example, the animal is a human.
[0165] Also provided is a polymer as defined above or a hydrogel as defined above or a composition as defined above for use in treating obesity, prediabetes, diabetes, non-alcoholic fatty liver disease (NAFLD) or chronic idiopathic constipation or for reducing caloric intake or improving glycemic control.
[0166] Also provided is the use of a polymer as defined above, or a hydrogel as defined above, or a composition as defined above, in the preparation of a medicament for treating obesity, prediabetes, diabetes, non-alcoholic fatty liver disease (NAFLD) or chronic idiopathic constipation, or for reducing caloric intake or improving glycemic control.
[0167] Also provided is a method for reducing weight or improving the body shape of a healthy subject, the method comprising the step of orally administering to the subject a polymer as defined above, or a hydrogel as defined above, or a composition as defined above.
[0168] Methods for weight loss or improving body shape can be purely cosmetic.
[0169] The amount of polymer or hydrogel or composition administered in the method for weight loss or for improving body shape may be the same as the amount of polymer or hydrogel or composition administered in the method for treating obesity as defined above.
[0170] The beneficial effects of the present invention are as follows: by using a long-interval cross-linking agent, the cross-linking with the polysaccharide chain can occur in a more flexible and diverse manner, thereby obtaining a polymer having a looser polymer network while still having a high strength level, promoting a larger swelling ratio of the hydrogel, and reducing the amount of cross-linking agent used in the reaction, reducing costs, introducing a polyethylene glycol additive, hindering the entanglement of the interval cross-linking agent, ensuring a higher mobility of the polymer space network, and thus ensuring a better swelling rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0171] The accompanying drawings illustrate the disclosed embodiments and serve to explain the principles of the disclosed embodiments. However, it should be understood that the accompanying drawings are designed for illustration purposes only and not as a definition of the limits of the present invention.
[0172] Figure 1
[0173] [ Figure 1] shows a schematic diagram showing the synthetic process of preparing a spacer crosslinker and a crosslinked CMC hydrogel. (101) indicates the reaction of preparing a spacer crosslinker, and (102) indicates the reaction of preparing a crosslinked carboxymethyl cellulose hydrogel.
[0174] Figure 2
[0175] [ Figure 2 ] shows a schematic diagram of the location of the intradermal injection site in the skin sensitization test. (202) indicates the cranial end, (204) indicates the caudal end, (206) indicates the 0.1 mL intradermal injection site, and (208) indicates the trimmed scapular area.
[0176] Figure 3
[0177] [ Figure 3 ] shows a schematic diagram comparing the cross-linking mechanisms of CMC hydrogel examples and controls. (302) indicates the reaction forming control C-1, (304) indicates the reaction forming examples 7 to 13, and (306) indicates the reaction forming control C-2. (310) indicates CMC, (312) indicates CA, (314) indicates PEG-CA, and (316) indicates PEG.
[0178] Example
[0179] Non-limiting embodiments of the present invention will be further described in more detail with reference to specific examples, which should not be construed in any way as limiting the scope of the present invention.
[0180] Material
[0181] Carboxymethylcellulose (CMC) sodium salt obtained from AQUALON TM7H3SF (Ashland Inc.), which has a viscosity of 1,000 to 2,800 cps as a 1% (wt / wt) aqueous solution at 25°C. Polyethylene glycol (PEG, average molecular weight of about 200, 400, 1K, 2K, 4K, 8K) was purchased from Sigma-Aldrich and used without further modification. Citric acid (CA) was obtained from Tokyo Chemical Industry (TCI) and used without further modification. Chemicals including sodium hypophosphite (SHP), sodium bicarbonate, disodium hydrogen phosphate, sodium chloride (NaCl) and sodium hydroxide (NaOH), hydrochloric acid (HCl) were purchased from Sigma-Aldrich and used as is. Sodium bicarbonate was combined with disodium hydrogen phosphate (1:1 by weight) to form a dual catalyst (CAT2) for esterification. Unless otherwise specified, deionized (DI) water with a resistivity of 18.2 Mohm-cm was used in all experiments and the procedures were performed at room temperature (23 ± 2°C).
[0182] Characterization methods
[0183] Esterification between PEG and CA (Calculation Method A)
[0184] Use base titration to confirm successful synthesis of the spacer crosslinker. Figure 1 , (101)), 3 mL (equivalent to 100 mg CA) of the resulting solution was diluted to 50 mL with DI water. A few drops of phenolphthalein ethanol (1:100) solution were added to the crosslinker solution, and then titrated with 0.1 N NaOH until the total solution color changed from clear to pink. The volume of NaOH consumed was recorded and compared with a control in which the same amount of PEG and CA were directly mixed. For example:
[0185] οThe initial input of CA was fixed at 1 g, and the equivalent concentration of COOH = 1000 / 192*3 = 15.6 mmol;
[0186] οPEG200 input was fixed at 0.5 g, and the equivalent concentration of OH = 500 / 200*2 = 5 mmol;
[0187] οThe initial inputs of PEG400, 1000, 2000, and 4000 were fixed at 1 g, 2.5 g, 5 g, and 10 g, respectively;
[0188] ο Theoretically, 100% esterification corresponds to a % reduction in COOH concentration = 5 / 15.6 = 32%;
[0189] o The actual degree of esterification can be estimated by dividing the actual % reduction in COOH concentration by 32%.
[0190] Swelling equilibrium
[0191] Media uptake measurements were performed on samples of dried cross-linked CMC in powder form (100 micron to 1000 micron particle size distribution) soaked in different media for 30 minutes. Standard simulated gastric fluid (SGF) was prepared by mixing 7 mL HCl 37%, 2 g NaCl, and 3.2 g pepsin in DI water. After the solids dissolved, more water was added to reach a volume of 1 L. Diluted SGF (Di-SGF) was prepared by mixing 1 part SGF with 8 parts DI water, and then simulating gastric fluid after water was ingested with pills / capsules containing dried cross-linked CMC.
[0192] The mediator uptake rate (MUR) of the cross-linked hydrogel in Di-SGF was determined as follows: a dry glass funnel was placed on a stand and 40 g of purified water was poured into the funnel. Once no additional drops were detected in the neck of the funnel (approximately 5 minutes), the funnel was placed in a dry empty glass beaker (beaker #1), which was placed on a tared scale to record the weight of the empty apparatus (W1). 40 g of DI-SGF solution was prepared as described above and placed in beaker #2. Using weighing paper, 0.25 g of cross-linked carboxymethyl cellulose powder was accurately weighed. The carboxymethyl cellulose powder was added to beaker #2 and gently stirred for 30 minutes with a magnetic stirrer without creating a vortex. The stirring bar was removed from the resulting suspension, the funnel was placed on a stand, and the suspension was poured into the funnel to allow the material to drain for 10 ± 1 minutes. The funnel containing the drained material was placed in beaker #1 and weighed (W2). The medium uptake rate (MUR) was calculated according to the following formula: MUR = (W2-W1) / 0.25. The assay was performed in triplicate.
[0193] Mechanical strength
[0194] The viscoelastic properties of the polymer hydrogels were determined according to the protocol set forth below. The hydrogels were freshly prepared according to the MUR test method described above to equilibrate the hydrogels. Briefly, 0.25 g of cross-linked carboxymethyl cellulose powder was soaked and stirred with 40 g of DI-SGF solution for 30 minutes. The swollen suspension was poured into a filter funnel and drained for 10 minutes, and the resulting hydrogel was collected for rheological testing.
[0195] Small deformation vibration measurements were performed using a rheometer (TADiscovery HR-30) equipped with a Peltier plate, an upper and lower plate with a diameter of 40 mm (with cross notches). All measurements were performed with a Peltier sensor at 25°C with a gap of 4 mm. The elastic modulus G' was obtained in the frequency range of 0.1 to 50 radians / second, and the strain was fixed at 0.1%. The hydrogel was subjected to a sweep frequency test using a rheometer, and the value at an angular frequency of 10 radians / second was determined. The determination was repeated three times. The reported G' value is the average of three determinations.
[0196] Nonclinical safety testing
[0197] The superabsorbent polymer thus prepared (Example 16 of Table 2) was weighed and poured into a gelatin capsule to form a single-use, ingestible, transient place-occupying medical device. With reference to ISO 10993 "Biological evaluation of medical device", the following biocompatibility and safety tests were evaluated and approved by an accredited laboratory before human trials:
[0198] In vitro cytotoxicity test
[0199] L929 mouse fibroblasts were obtained from ATCC (American Type Culture Collection, USA).
[0200] Four SAP capsules (containing a total of 2.24 g) were dissolved in 500 mL of MEM and spread onto a 10 mm × 10 mm filter membrane to form a SAP test sample. The negative control used was high-density polyethylene from the United States Pharmacopeial Convention (USP). The positive control used was natural latex gloves. Each control sample was prepared as a 10 mm × 10 mm sample.
[0201] Cell culture was handled using sterile procedures. L929 cells were cultured in minimum essential medium (MEM) (90% fetal bovine serum (FBS), penicillin 100 U / mL, streptomycin sulfate 100 μg / mL) at 37°C in a humidified atmosphere of 5% CO2, and then digested with 0.25% trypsin containing ethylenediaminetetraacetic acid (EDTA) to obtain 1.0×10 5 The suspended cells were dispensed at 2 mL per container. Cell morphology was evaluated to verify that the monolayer was satisfactory after incubation at 37°C in 5% CO2 for 24 hours.
[0202] After the cells grow to form a monolayer, the initial cell culture medium is discarded. Then 2 mL of fresh culture medium is added to each container. The SAP test sample is placed on the cell layer at the center of each parallel determination container to ensure that the SAP test sample covers about one-tenth of the cell layer surface. In a similar manner, parallel determination containers for both negative control and positive control materials are prepared. Three parallel determination products of each group are tested.
[0203] After 48 hours of incubation, the test sample outline was marked on the bottom of the culture dish with a permanent marker and the test sample was removed. The culture medium was aspirated and 500 μL of neutral red solution was added to each plate and incubated for 1 hour. The neutral red solution was discarded and 2 mL of phosphate buffered saline (PBS) was added and each culture was examined microscopically. Using the criteria in Table A, changes such as general morphology, vacuolization, shedding, cell lysis, and membrane integrity were evaluated.
[0204] Table A. Reactivity Ratings
[0205]
[0206]
[0207] Based on Table A, value ranges greater than 2 were considered cytotoxic.
[0208] Skin allergy test
[0209] According to ISO 10993-10:2010 "Part 10: Tests for irritation and skinsensitization", SAP samples were extracted into 0.9% sodium chloride or sesame oil in a guinea pig maximum test and the extracts were evaluated to determine whether components extracted from the SAP samples could cause skin sensitization.
[0210] 0.9% Sodium Chloride Injection Extract
[0211] The negative control was 0.9% sodium chloride injection obtained from Guangxi Yuyuan Pharmaceutical Co., Ltd., and the positive control was 2,4-dinitrochlorobenzene (DNCB) obtained from Chengdu Aikeda Chemical Reagent Co., Ltd. 0.9% sodium chloride injection is a 0.9% sodium chloride aqueous solution.
[0212] Under sterile conditions, the samples were extracted using the total sampling method, wherein an additional volume of extraction medium was added when the extraction was performed, wherein the extraction medium was absorbed by the test sample. The extraction was performed in a closed inert container with stirring according to the extraction ratio (sample: extraction medium) listed in Table B. The extraction medium was 0.9% sodium chloride injection.
[0213] Table B. Extraction using 0.9% sodium chloride injection
[0214]
[0215] Vehicle (no SAP sample) was prepared similarly to serve as a control.
[0216] Sesame Oil Extract
[0217] The negative control was sesame oil (SO) obtained from Ji'an Qingyuan District Luyuanxiangliao. Co. Ltd., and the positive control was 2,4-dinitrochlorobenzene (DNCB) obtained from Chengdu Aikeda Chemical Reagent Co., Ltd.
[0218] The samples were taken under sterile conditions using the total sampling method. The extraction was performed in a closed inert container with stirring according to the extraction ratios (sample: extraction solvent) listed in Table C. The extraction solvent was sesame oil (SO).
[0219] Table C. Extraction using sesame oil
[0220]
[0221] Vehicle (no SAP sample) was prepared similarly to serve as a control.
[0222] test
[0223] Healthy male Hartley guinea pigs (Cavia Porcellus) obtained from Suzhou Experimental Animal Sci-Tech Co., Ltd. (license code: SCXK (SU) 2020-0007) were used to evaluate skin sensitization. The initial weight of each animal was 300 g to 500 g. The animals were healthy and had not been used in experimental procedures before, and were raised in corn cob litter (Suzhou Shuangshi Laboratory Animal Feed Science Co., Ltd.) with a 12-hour light / dark cycle with full-spectrum lighting at a temperature of 18°C to 26°C and a humidity of 30% to 70%, and fed with guinea pig feed (Suzhou Experimental Animal Sci-Tech Co., Ltd.).
[0224] For each experiment based on 0.9% sodium chloride injection extract or sesame oil extract, 15 guinea pigs were weighed and identified on the first day of treatment. The fur of the dorsal scapular region of the animals was removed with electric clippers and the animals were grouped so that 10 animals were exposed to SAP samples and 5 animals were exposed to negative controls.
[0225] I. Intradermal Induction Phase I
[0226] In the trimmed scapular area, Figure 2 Each animal received a pair of 0.1 mL intradermal injections at each of the indicated injection sites (A, B, and C).
[0227] Part A: A 50:50 (V / V) stable emulsion of Freund's complete adjuvant mixed with a selected solvent.
[0228] Site B: Test sample (undiluted extract): Control animals were injected with solvent only.
[0229] Site C: The test sample at the same concentration as that used in site B was emulsified with a 50:50 (V / V) stable emulsion of Freund's complete adjuvant and solvent; control animals were injected with an emulsion of blank liquid and adjuvant.
[0230] II. Intradermal Induction Phase II
[0231] The maximum concentration that can be achieved without causing irritation in intradermal induction phase I. Animals were treated with 10% dodecyl sulfate (solvent: distilled water) 24±2 hours before topical induction application.
[0232] 7 ± 1 days after the intradermal induction period, use approximately 8 cm 20.5 mL of the SP sample extract was applied topically to the scapular region of each animal using a patch (in absorbent gauze) of 1.5 mm2 (0.5 mm2) area so as to cover the intradermal injection site. The patch was fixed with an occlusive dressing. The dressing and patch were removed after 48 ± 2 hours. Control animals were treated similarly with blank liquid alone.
[0233] III. Attack period
[0234] All test and control animals were challenged with SAP samples 14 ± 1 days after the completion of the topical induction period. Absorbent gauze (8 cm 2 ), 0.5 mL of the test sample extract and the control sample were applied topically to the site that was not treated during the induction period. The site was fixed with an occlusive dressing, and the dressing and patch were removed after 24±2 hours.
[0235] The appearance of the challenged skin sites of the test and control animals was observed 24±2 hours and 48±2 hours after removal of the dressing. Full spectrum lighting was used to visualize the skin reactions. The skin reactions of erythema and edema were described and graded according to the Magnusson and Kligman scale.
[0236] Oral Allergy Test
[0237] According to ISO 10993-10:2010 "Part 10: Tests for irritation and skinsensitization", SAP samples were extracted into 0.9% sodium chloride or sesame oil, and the extracts were evaluated to determine whether the components extracted from the SAP samples would cause oral sensitization in hamsters.
[0238] 0.9% Sodium Chloride Injection Extract
[0239] The negative control was 0.9% sodium chloride injection obtained from Guangxi Yuyuan Pharmaceutical Co., Ltd.
[0240] Under sterile conditions, samples were taken using the total sampling method, wherein an additional volume of extraction medium was added when performing the extraction, wherein the extraction medium was absorbed by the test sample. The extraction was performed in a closed inert container with stirring according to the extraction ratio (sample: extraction medium) listed in Table D. The extraction medium was 0.9% sodium chloride injection.
[0241] Table D. Extraction using 0.9% sodium chloride injection
[0242]
[0243] Vehicle (no SAP test sample) was prepared similarly to serve as a control.
[0244] Sesame Oil Extract
[0245] The negative control was sesame oil (SO) obtained from Ji'an Qingyuan District Luyuanxiangliao. Co. Ltd.
[0246] The samples were taken under sterile conditions using the total sampling method. The extraction was performed in a closed inert container with stirring according to the extraction ratios (sample: extraction solvent) listed in Table E. The extraction solvent was sesame oil (SO).
[0247] Table E. Extraction using sesame oil
[0248]
[0249] Vehicle (no SAP test sample) was prepared similarly to serve as a control.
[0250] test
[0251] Healthy male hamsters (license code: SCXK (JING) 2016-0011) obtained from Beijing Vital River Laboratory Animal Technologies Co., Ltd. were used to evaluate oral sensitization. The initial body weight of each animal was 109 g to 129 g. The animals were healthy and had not been used in experimental procedures before, and were raised in corn cob litter (Suzhou Shuangshi Laboratory Animal Feed Science Co., Ltd.) with a 12-hour light / dark cycle with full-spectrum lighting at a temperature of 18°C to 26°C and a humidity of 30% to 70%, and were fed with irradiated sterilized feed (Suzhou Shuangshi Laboratory Animal Feed Science Co., Ltd.).
[0252] For each experiment based on 0.9% sodium chloride injection extract or sesame oil extract, 6 animals were weighed and identified. The cheek pouches of the animals were inverted and washed with 0.9% sodium chloride injection and examined for any abnormalities. A cotton ball was soaked in the SAP sample and placed in one pouch of each animal. No sample was placed in the other pouch, which served as a control. The exposure duration was 5 minutes. After exposure, the cotton ball was removed and the pouch was washed with 0.9% sodium chloride injection, taking care not to contaminate the other pouch. The procedure was repeated every 1 hour for a duration of 4 hours. Control animals were treated similarly with a separate negative control sample. The appearance of the cheek pouch of each animal was described, and the erythema of the pouch surface reaction was graded.
[0253] Cheek pouches were macroscopically examined 24 ± 2 hours after final treatment and hamsters were humanely sacrificed to remove tissue samples from representative pouch areas. Tissue samples were placed in 4% formaldehyde for histological examination prior to treatment. After fixation, specimens were trimmed, embedded, sectioned, and stained with hematoxylin and eosin (H&E) stain. Irritant effects on stained oral tissues were evaluated microscopically.
[0254] Acute systemic toxicity test
[0255] According to ISO 10993-11:2017 “Part 11: Tests for systemic toxicity”, SAP samples were extracted into 0.9% sodium chloride or sesame oil, and the extracts were evaluated to determine whether the components extracted from the SAP samples would cause acute systemic toxicity after injection into mice.
[0256] 0.9% Sodium Chloride Injection Extract
[0257] The negative control was 0.9% sodium chloride injection obtained from Guangxi Yuyuan Pharmaceutical Co., Ltd.
[0258] Under sterile conditions, samples were taken using the total sampling method, where an additional volume of extraction medium was added when performing the extraction, where the extraction medium was absorbed by the test sample. The extraction was performed in a closed inert container with stirring according to the extraction ratio (sample: extraction medium) listed in Table F. The extraction medium was 0.9% sodium chloride injection.
[0259] Table F. Extraction using 0.9% sodium chloride injection
[0260]
[0261] Vehicle (no SAP test sample) was prepared similarly to serve as a control.
[0262] Sesame Oil Extract
[0263] The negative control was sesame oil (SO) obtained from Ji'an Qingyuan District Luyuanxiangliao. Co. Ltd.
[0264] The samples were taken under sterile conditions using the total sampling method. The extraction was performed in a closed inert container with stirring according to the extraction ratios (sample: extraction solvent) listed in Table G. The extraction solvent was sesame oil (SO).
[0265] Table G. Extraction using sesame oil
[0266]
[0267] Vehicle (no SAP test sample) was prepared similarly to serve as a control.
[0268] test
[0269] Healthy male ICR mice (license code: SCXK (Zhe) 2019-0001) obtained from Zhejiang Vital River Laboratory Animal Technology Co., Ltd. were used to evaluate acute systemic toxicity. The initial body weight of each animal was 18 g to 22 g. The animals were healthy and young and had not been used in experimental procedures before, and were raised in corn cob litter (Suzhou Experimental Animal Sci-Tech Co., Ltd.) with a 12-hour light / dark cycle with full-spectrum lighting at a temperature of 20°C to 26°C and a humidity of 30% to 70%, and were fed with guinea pig feed (Suzhou Experimental Animal Sci-Tech Co., Ltd.).
[0270] For each experiment based on 0.9% sodium chloride injection extract or sesame oil extract, on the first day of treatment, 10 animals were weighed and identified, and grouped so that 5 animals were exposed to SAP samples and 5 animals were exposed to negative controls. A single dose of the test sample extract was administered to the designated group of mice by gavage at a dose of 50 mL / kg. The negative control was administered similarly to the control group. After sample administration, food was withheld for another 3 to 4 hours.
[0271] Mice were observed for any adverse clinical reactions immediately after injection and the animals were returned to their cages. Animals were observed for signs of systemic reactions at 4, 24, 48 and 72 hours after administration and weighed daily for three days after administration. Any animal found dead or with abnormal signs was subjected to gross necropsy.
[0272] If none of the mice treated with the test article extract showed significantly greater biological reactivity than the control mice during the observation period of the acute systemic toxicity test, the SAP test sample was considered to meet the requirement of no acute systemic toxicity. If two or more animals died, or if two or more animals showed abnormal behavior (such as convulsions or collapse), or if three or more animals showed more than 10% weight loss, the SAP sample was considered to be unqualified and was considered to have acute systemic toxicity.
[0273] Example 1: Synthesis
[0274] Synthesis of spacer crosslinking agent using catalyst (step 1, Figure 1 (101))
[0275] Citric acid (CA, 1 g) and catalyst (SHP or CAT2, 0.5 g) are dissolved in 10 mL DI water. PEG with different lengths is weighed and gradually added to the CA solution. The completely dissolved solution is loaded into a flask of a rotary evaporator (IKA) with a silicone oil bath. The solution in the rotary flask is heated at 100 ° C for 0.5 hours, and then the oil bath temperature is gradually increased to 120 ° C. Without condensation, all water in the flask is evaporated after 2 hours, producing a viscous yellow paste in the flask. Once cooled to room temperature (RT), the resulting paste is further diluted with DI water to form a 30 mL sample, of which 1.5 mL or 3 mL (equivalent to 50 mg or 100 mg CA, respectively) is used for further cross-linking reaction or titration.
[0276] Synthesis of spacer crosslinker without catalyst (step 1, Figure 1 (101))
[0277] Citric acid (CA, 1 g) was dissolved in 10 mL DI water, and then PEG with different lengths was weighed and mixed with the CA solution. The completely dissolved solution was loaded into a flask of a rotary evaporator (IKA) with a silicone oil bath. The solution in the rotary flask was heated at 100 ° C for 0.5 hours, and then the oil bath temperature was gradually increased to 120 ° C. Without condensation, all water in the flask was evaporated after 2 hours, producing a viscous yellow paste in the flask. Once cooled to room temperature, the resulting viscous paste was dissolved in DI water to form a 30 mL solution, of which 1.5 mL or 3 mL (equivalent to 50 mg or 100 mg CA, respectively) was used for further cross-linking reactions and titrations.
[0278] Preparation of cross-linked carboxymethyl cellulose hydrogel without polymer additives (step 2, Figure 1 (102))
[0279] DI water (400mL to 700mL) was added to a 1L beaker and stirred at 60rpm with an ANGNI electric stirrer. A spacer crosslinker solution with an equivalent citric acid content (equivalent to 50mg or 25mg CA) was added to the water. CMC (10g) was then added to the solution, and the resulting mixture was stirred at 120rpm for 2 hours at room temperature, and then at 60rpm for 24 hours. The final homogenized solution was poured into a stainless steel tray with a solution thickness of less than 2cm. The tray was placed in a convection oven (Lantian) at 50°C for 24 hours. The tray was removed from the oven, the dried CMC sheet was inverted, and the tray was returned to the oven and maintained at 50°C for 12 to 24 hours until no weight change was observed.
[0280] After complete drying, the CMC sheet is ground by means of a cutting blender (Philips). The granular material is sieved to a particle size of 0.1mm to 2mm, then spread onto a tray and crosslinked in a convection oven (Binder) at 120°C for 2 to 4 hours. The crosslinked polymer hydrogel thus obtained is washed with DI water for 4 to 12 hours, and the washing solution is replaced 3 times to remove unreacted reagents. The washing stage increases the medium uptake capacity of the hydrogel by increasing the relaxation of the network. After washing, the hydrogel is placed on a tray and placed in an oven (Lantian) at 50°C for 12 to 24 hours until no weight change is observed. The dried hydrogel aggregates are ground and sieved to a particle size of 0.1mm to 1mm. Unless otherwise specified, the polymer of the present invention is used as is (without further treatment) to perform the experiments described below. However, the polymer of the present invention can be poured into a gelatin capsule and sealed for further biomedical research.
[0281] Preparation of cross-linked carboxymethyl cellulose hydrogels using polymer additives
[0282] To prepare cross-linked carboxymethylcellulose hydrogels with polymer additives, a similar procedure to the preparation of cross-linked carboxymethylcellulose hydrogels without polymer additives was used, except that PEG oligomers (100 mg to 300 mg) were added to water along with the spacer cross-linker and citric acid before adding CMC. All subsequent procedures were repeated in the same manner.
[0283] Large-scale preparation of cross-linked carboxymethyl cellulose hydrogels
[0284] Large-scale preparation of cross-linked carboxymethylcellulose hydrogels with polymer additives was performed as follows:
[0285] Citric acid (CA, 5 g) was dissolved in 50 mL of DI water. PEG4000 (50 g) was then added to the CA solution. The completely dissolved solution was charged into a flask of a rotary evaporator and heated at 98°C for 8 hours, and the resulting paste was completely dissolved in DI water to form 200 mL of a spacer crosslinker solution.
[0286] DI water (6 L) was added to a 10 L container and stirred at 60 rpm. Spacer crosslinker solution (20 mL), CMC (100 g) and PEG200 (1 g) were added, and the resulting mixture was stirred at 100 rpm for 24 hours at room temperature to obtain a homogenized solution. The homogenized solution was poured into a stainless steel tray, and the tray was placed in a convection oven at 80 ° C for 24 hours to obtain a dried composite sheet. The dried composite sheet was then mechanically ground and sieved into sieved particles having a size of about 1.0 mm. The sieved particles were then heated at 100 ° C for 8 hours to obtain a cross-linked hydrogel.
[0287] Example 2: Analysis of spacer crosslinkers
[0288] Table 1 shows the reaction of step 1 ( Figure 1 , (101)) and the titration summary of the spacer crosslinker after and the corresponding mixture control in which equal amounts of the components were simply mixed without covalent bonding. Specifically, PEG-CA represents a spacer crosslinker in which PEG and CA are covalently bonded, while PEG+CA represents a mixture control in which PEG and CA are simply mixed. The number indicated after PEG (200, 400, 1000, 2000) indicates the molecular weight of PEG.
[0289] Compared to the mixture control in which PEG and CA were simply mixed, the significantly reduced volume of base required during the titration showed successful esterification between the PEG hydroxyl group and the CA carboxylic acid group. Taking PEG200-CA and PEG200+CA (mixture control) without a catalyst as examples, it can be seen that the mixture control consumed 17.2 mL of 0.1 N NaOH, which is almost the same as the pure CA control without PEG200. In contrast, in step 1 reaction ( Figure 1 , (101)), the volume of 0.1 N NaOH required for titration was reduced to 12.0 mL. Using calculation method A (indicated above under Characterization methods for esterification between PEG and CA), the estimated degree of esterification of PEG200-CA was found to be about 94%.
[0290] The step 1 reaction using a catalyst ( Figure 1 , (101)) were compared similarly. ":SHP" or ":CAT2" indicates that the spacer crosslinker was formed in the presence of the corresponding catalyst. For PEG200-CA with SHP as catalyst (PEG200-CA:SHP) and PEG400-CA with SHP as catalyst (PEG400-CA:SHP), the degrees of esterification were found to be about 84 and 87%, respectively.
[0291] There is no clear evidence that the efficiency of the esterification process with a catalyst is better than that without a catalyst. For example, the degree of esterification of PEG400-CA with and without SHP was 86.3% and 98.7%, respectively. SHP is known to weaken the hydrogen bonds between the carboxylic acid groups of CA, which helps to accelerate the anhydride formation at low temperatures. SHP also accelerates the formation of anhydride intermediates from amorphous polycarboxylic acids. In the past, dual catalyst CAT2 was involved in the esterification of cellulose or PEG, but it was difficult to quantify the step 1 reaction ( Figure 1 , (101)), because the sodium bicarbonate in CAT2 reacts immediately with CA to generate carbon dioxide bubbles. The mixture control of PEG200+CA+CAT2 consumed only 13.2 mL of NaOH. Another component in CAT2, disodium hydrogen phosphate, can form a McIlvaine buffer with CA and significantly interfere with the true neutralization point during the base titration. Therefore, if calculation method A (indicated above under the characterization method of esterification between PEG and CA) is applied to PEG200-CA:CAT2, an artificial degree of esterification exceeding 100% is observed, as indicated by (*) in Table 1.
[0292] Table 1: Summary of base titrations of spacer crosslinkers and corresponding mixture controls
[0293]
[0294] *Indicates a degree of esterification greater than 100%, which is an experimental / calculation artifact.
[0295] Example 3: Analysis of CMC hydrogels using spacer crosslinkers
[0296] The PEG-CA spacer solution obtained with or without catalyst was directly used in step 2 CMC cross-linking process ( Figure 1 , (102)). No further purification was performed because small amounts of unreacted CA and PEG could participate in the subsequent high-temperature cross-linking process and unreacted catalyst could be removed during the hydrogel washing process. Table 2 summarizes the properties of cross-linked CMC (X-CMC) hydrogels with spacer cross-linkers under various conditions (including the use of equivalent CA / CMC wt%, PEG-CA cross-linkers with different PEG chain lengths, cross-linkers with or without catalysts, cross-linking temperature and time). The two most important parameters, namely water absorption (MUR) and mechanical strength (G'), were measured to evaluate the performance of the hydrogels. Several key conclusions about the design and fabrication of the hydrogels can be drawn from Table 2.
[0297] Effect of equivalent CA / CMC wt% on MUR of hydrogels
[0298] In step 2 reaction ( Figure 1 , (102)), the CA / CMC wt% ratio was adjusted by adding different volumes of spacer crosslinker solution (e.g., 1.5 mL PEG-CA, equivalent to 50 mg CA) to a solution of a fixed amount of CMC (10 g), followed by drying and crosslinking processes to obtain hydrogels. A significant trend was observed when the equivalent CA wt% in the spacer crosslinker solution was reduced from 1% to 0.25%, whereby the MUR of the hydrogel was found to increase from <30 to >90. A similar trend was previously observed when pristine CA was used as a crosslinker. A lower CA wt% means that fewer crosslinking reactions occur between the CA carboxylic acid groups and the CMC hydroxyl groups, resulting in a lower degree of crosslinking and a looser polymer network. For hydrogels, a looser polymer network generally results in a greater water absorption or swelling ratio. Even though the molecular size of the PEG-CA crosslinker of the present invention is much larger than that of the CA molecule, the crosslinking reaction still occurs between the carboxylic acid end groups of PEG-CA and the hydroxyl groups of the CMC backbone. A more accurate estimate of the degree of cross-linking of CMC can be determined by the free carboxylic acid groups present on the termini of the PEG-CA cross-linker, since during step 1 the esterification process ( Figure 1, (101)) during the reaction, about one-third (1 / 3) of the carboxylic acid groups of CA are consumed. For example, one original CA molecule has three COOH groups and two CA molecules have six COOH groups. After esterification, one PEG-CA cross-linker contains PEG covalently bonded to two CAs at both ends, and each PEG-CA cross-linker will have only four free COOH groups because the third COOH group on each CA molecule will react to form a covalent bond with PEG. In this regard, Table 1 also shows the titrated NaOH volume of the corresponding mixture control, which indicates the amount of free COOH groups available for the cross-linking process.
[0299] Effect of Catalyst on MUR of Hydrogel
[0300] Similar to step 1 esterification ( Figure 1 , (101)) As a result, there is no clear evidence that the catalyst added to the crosslinker solution contributes to any favorable hydrogel properties. Comparing Example 4 and Example 7 in Table 2, the MUR of CMC crosslinked with PEG200-CA (equivalent to 50 mg CA) with and without SHP is similar. The same is true for CMC hydrogels crosslinked with PEG400-CA (Examples 6 and 8 in Table 2). From an economic and commercial perspective, this shows that catalysts are not required for large-scale production of hydrogels.
[0301] It is worth mentioning the comparison between the examples catalyzed by SHP and CAT2, such as Example 2 and Example 3, or Example 4 and Example 5 of Table 2. Even though the initial PEG-CA crosslinkers used in these examples had the same equivalent CA wt%, the absorption capacity of the resulting hydrogels was very different. Specifically, Example 2 of Table 2 using SHP had a MUR of about 24, while Example 3 of Table 2 using CAT2 had a MUR of about 52. This can be explained by the titrated NaOH volume in the crosslinker solution. Due to the effects of sodium bicarbonate and phosphate buffers as mentioned above, fewer COOH groups were retained in CAT2 when used for the PEG-CA crosslinker reaction, resulting in a lower crosslinking density in the resulting hydrogel.
[0302] Effect of PEG on MUR and G' of Hydrogels
[0303] When long hydrophilic crosslinkers such as PEG are used, one end of the crosslinker reacts with the CMC chain, and due to the flexible nature of the polymer chains in the crosslinker, the other end can move around and have a higher chance of reacting with another CMC chain located further away. This overcomes the problem of low mobility when short crosslinkers such as CA are used. Therefore, the robust but loose hydrogel network achieved using long hydrophilic crosslinkers tends to have a higher elastic modulus coupled with higher water absorption.
[0304] This feature is well demonstrated by the examples in Table 2. Compared to the C-1 control hydrogel crosslinked with CA, Examples 11 to 14 using spacer crosslinkers with the same equivalent CA / CMC ratios show significantly higher MUR and G'.
[0305] In addition, it was observed that spacer crosslinkers with higher molecular weight or longer chain lengths resulted in hydrogels with higher MUR: Example 14 of Table 2 with PEG2000 showed a MUR of about 140, while Example 11 of Table 2 with PEG200 showed a MUR of about 90. As mentioned above, the use of longer hydrophilic crosslinkers will result in a looser polymer network and therefore higher water absorption. However, the correlation between the crosslinker PEG length and the elastic modulus G' of the hydrogel is not linear: Example 12 of Table 2 with PEG400 showed a G' of about 2300, while Example 14 of Table 2 with PEG2000 had a G' of about 1600. From the comparison of the MUR values of Examples 11 to 14 of Table 2, it can be seen that the mechanical strength of the hydrogel is more sensitive and inversely correlated with the water absorption.
[0306] It should also be noted that for a simple mixture of PEG2000+CMC+CA (control C-2), the MUR is about 80 and the G' is about 1300. Figure 3 The schematic diagram of the cross-linking mechanism shown also explains the difference in properties. For control C-2, random esterification occurred between the hydroxyl groups of CMC / PEG and the carboxylic acid groups of the CA molecules. Considering that the CMC polymer backbone contains a significantly larger number of pendant hydroxyl groups compared to the terminal hydroxyl groups of PEG, most of the esterification reaction in control C-2 occurred between CMC and CA, resulting in similar cross-linking as control C-1. In control C-2, only a small amount of PEG was cross-linked into the CMC network, which would change the rheological properties of the hydrogel.
[0307] Table 2: Summary of cross-linked CMC and CA comparisons using spacer cross-linkers
[0308]
[0309] Example 4: Non-clinical safety testing
[0310] The superabsorbent polymer thus prepared (Example 16 of Table 2) was weighed and poured into a gelatin capsule to form a single-use, ingestible, transient place-occupying medical device. It was classified as a mucosal contact device because it involves repeated, long-term contact during use (>24 hours, <30 days). The following biocompatibility and safety tests were evaluated and approved by an accredited laboratory before human trials:
[0311] In vitro cytotoxicity
[0312] In vitro cytotoxicity was evaluated using the mammalian cell culture (L929) direct contact method according to ISO 10993-5:2009 “Part 5: Tests for in vitro cytotoxicity”.
[0313] The results are shown in Tables 3 and 4.
[0314] Table 3. Observation of cell morphology
[0315]
[0316] Table 4. Cellular reactivity
[0317]
[0318] Under the tested conditions, the SAP samples showed no potential toxicity to L929 cells.
[0319] Skin sensitization
[0320] Skin sensitization testing (0.9% NaCl and sesame oil extract) was performed according to ISO 10993-10:2010 "Part 10: Tests for irritation and skinsensitization" using the guinea pig maximum test.
[0321] 0.9% Sodium Chloride Injection Extract
[0322] No skin sensitization reaction was found in guinea pig skin using the SAP sample extract, and the sensitization positive rate was 0%. The sensitization positive rate in the positive control group was 100%.
[0323] Sesame Oil Extract
[0324] No skin sensitization reaction was found in guinea pig skin using the SAP sample extract, and the sensitization positive rate was 0%. The sensitization positive rate in the positive control group was 100%.
[0325] Oral mucosal irritation
[0326] Oral mucosal irritation testing (0.9% NaCl and sesame oil extract) was performed on hamsters according to ISO 10993-10:2010 "Part 10: Tests for irritation and skinsensitization".
[0327] 0.9% Sodium Chloride Injection Extract
[0328] Under the experimental conditions, the SAP samples did not show any significant evidence of causing irritation to the oral mucosa of hamsters.
[0329] Microscopic histopathological evaluation showed that in the oral mucosal structure of the test group and the control group, the stratified squamous epithelium and the lamina propria were in normal condition. In the stratified squamous epithelium, each layer of cells was normal and intact, and no leukocyte infiltration, vascular congestion and edema were observed. The lamina propria of the test group and the control group was normal and intact, and no leukocyte infiltration, vascular congestion and edema were observed. In the lamina propria of the test group and the control group, there was no edema in the walls of small blood vessels, partial tube coagulation was observed in a small number of red blood cells, and no leukocyte infiltration was observed in the surrounding blood vessels. Salivary glands were visible in the lamina propria of the test group and the control group, and the salivary gland structure was normal and intact, the alveoli were not enlarged, and no leukocyte infiltration and edema were observed around the alveoli. No deformation, leukocyte infiltration or edema was observed in the skeletal muscle fibers under the oral mucosa of the test group and the control group.
[0330] Sesame Oil Extract
[0331] Under the experimental conditions, the SAP samples did not show any significant evidence of causing irritation to the oral mucosa of hamsters.
[0332] Microscopic histopathological evaluation showed that in the oral mucosal structure of the test group and the control group, the stratified squamous epithelium and the lamina propria were in normal condition. In the stratified squamous epithelium, each layer of cells was normal and intact, and no leukocyte infiltration, vascular congestion and edema were observed. The lamina propria of the test group and the control group was normal and intact, and no leukocyte infiltration, vascular congestion and edema were observed. In the lamina propria of the test group and the control group, there was no edema in the walls of small blood vessels, partial tube coagulation was observed in a small number of red blood cells, and no leukocyte infiltration was observed in the surrounding blood vessels. Salivary glands were visible in the lamina propria of the test group and the control group, and the salivary gland structure was normal and intact, the alveoli were not enlarged, and no leukocyte infiltration and edema were observed around the alveoli. No deformation, leukocyte infiltration or edema was observed in the skeletal muscle fibers under the oral mucosa of the test group and the control group.
[0333] Acute systemic toxicity
[0334] Acute systemic toxicity testing (0.9% NaCl and sesame oil extract) was performed on mice by oral administration / gavage according to ISO 10993-11:2017 “Part 11: Tests for systemic toxicity”.
[0335] 0.9% Sodium Chloride Injection Extract
[0336] All animals were clinically normal throughout the study. Body weight data were acceptable and equivalent between the test and control treatment groups.
[0337] Sesame Oil Extract
[0338] All animals were clinically normal throughout the study. Body weight data were acceptable and equivalent between the test and control treatment groups.
[0339] Example 5: Human Volunteer Study
[0340] To verify the efficacy of superabsorbent polymer hydrogel (SAP) for treating overweight and obesity, a capsule device containing SAP Example 16 of Table 2 was tested using two middle-aged healthy but overweight female volunteers with a BMI of about 28, one of whom was administered SAP and the other was administered a placebo. The volunteers received a normal average mixed diet and were monitored for 12 weeks.
[0341] For administration, volunteer I consumed 500 mL of water with 4 capsules (containing a total of 2.24 g of SAP Example 16 of Table 2) at least 30 minutes before each meal, and volunteer II consumed 500 mL of water with 4 capsules (containing a total of 2.24 g of food grade sugar). Both volunteers were prescribed a 300 kcal / day hypocaloric diet (lower than their calculated energy requirements) and were instructed to perform moderate intensity exercise daily, such as walking for 30 minutes daily during the study period.
[0342] As shown in Table 5, after 12 weeks, significant weight changes were observed for Volunteer I compared to Volunteer II (6.3% and 2.0%, respectively) despite their initial body mass index (BMI) of about 28. The significant increase in weight loss for Volunteer I can be attributed to the SAP hydrogel, which acted as a gastric spacer and helped Volunteer I to easily control food intake. Volunteer II demonstrated that a healthy lifestyle such as dietary control and exercise did help to some extent, but additional measures were needed to enhance the weight loss effect to achieve the widely accepted -5% response rate.
[0343] During the study, the volunteers' bowel movement frequency and quality of life scores were recorded to explore the effect of SAP on functional constipation. Chronic constipation is a common condition characterized by infrequent bowel movements, hard stools, and difficult defecation. Constipation is traditionally treated with fiber, osmotic agents, and stimulants (such as psyllium, polyethylene glycol, and bisacodyl, etc.).
[0344] As shown in Table 5, volunteer I experienced more frequent and more regular defecation after being administered with SAP capsules.Quality of life was measured with reference to the impact of modified SF-36 health survey and weight on quality of life (Impact of Weight on Quality of Life-Lite).The modified SF-36 evaluated 8 areas (physical function, physiological function, somatic pain, general health, vitality, social function, emotional function, mental health), and the score range was 0 (worst health status) to 10 (best health status).The review in the investigation shows that during the research period, the constipation symptoms of volunteer I were much less than volunteer II, which corresponds to their quality of life score.The scientific explanation of the function of SAP in constipation is due to its water storage and water retention capacity.SAP hydrogel can be partially degraded by the bacteria in the colon, so water and cellulose fibers that help to improve constipation can be released.
[0345] Table 5. Comparison of the effects of SAP on human subjects and controls
[0346]
[0347] Industrial Applicability
[0348] The present invention can be used in personal disposable hygiene products (such as baby diapers, adult diapers and sanitary napkins, etc.), blocking water penetration in underground power or communication cables, self-repairing concrete, water retaining agents for gardening, controlling spills and waste of aqueous fluids, and artificial snow for film and stage productions.
[0349] The present invention can also be used to treat obesity, prediabetes, diabetes, non-alcoholic fatty liver disease, chronic idiopathic constipation, and to reduce caloric intake or improve blood sugar control. The present invention can also be used in a method of reducing weight or improving the body shape of a healthy subject.
[0350] Obviously, various other modifications and adaptations of the present invention will become apparent to those skilled in the art after reading the foregoing disclosure without departing from the spirit and scope of the invention, and all such modifications and adaptations are intended to fall within the scope of the appended claims.
Claims
1. A method for preparing a superabsorbent hydrogel, characterized in that: The following steps are involved: 1) esterifying a first optionally substituted aliphatic molecule comprising at least two hydroxyl groups with a second molecule comprising at least three carboxylic acid groups at a temperature of 80° C. to 180° C. to form a spacer crosslinker; 2) mixing the spacer cross-linking agent, polyethylene glycol and polysaccharide in a solvent to form a homogenized mixture; 3) drying the homogenized mixture at a temperature in the range of 40° C. to 90° C. to remove the solvent; 4) grinding the dried homogenized mixture to form a powder having a particle size ranging from 0.05 mm to 5 mm; wherein the first optionally substituted aliphatic molecule comprising at least two hydroxyl groups is selected from one of polyether, polyacrylamide, polyethyleneimine, polyacrylate, polymethacrylate, polyethylene glycol, polyvinylpyrrolidone and polyvinyl alcohol; The second molecule comprising at least three carboxylic acid groups is selected from one of citric acid, pyromellitic acid, butanetetracarboxylic acid and benzoquinonetetracarboxylic acid; The polysaccharide is selected from starch, cellulose, galactomannan and alginate.
2. The method for preparing the superabsorbent hydrogel according to claim 1, characterized in that: The cellulose is selected from carboxymethyl cellulose and carboxymethyl cellulose sodium salt.
3. The method for preparing the superabsorbent hydrogel according to claim 1, characterized in that: The weight ratio of the second molecule comprising at least three carboxylic acid groups to the polysaccharide is less than 1:
30.
4. The method for preparing the superabsorbent hydrogel according to claim 1, characterized in that: The reaction temperature was heated step by step, first to 100°C and then gradually increased to 120°C.
5. The method for preparing the superabsorbent hydrogel according to claim 1, characterized in that: Includes steps: 1) dissolving citric acid in water to form a solution, then adding polyethylene glycol to the solution to obtain a mixed solution, heating the mixed solution at 100° C. for a period of time, then gradually increasing the temperature to 120° C. to obtain a paste by reaction, and adding water to dissolve the paste to obtain a spacer crosslinker solution; 2) adding the spacer crosslinker solution having an equivalent citric acid content and polyethylene glycol to water, and then adding carboxymethyl cellulose to form the homogenized mixture.
6. A superabsorbent hydrogel, characterized in that: The superabsorbent hydrogel is prepared by the preparation method of the superabsorbent hydrogel according to any one of claims 1 to 5.
7. Use of the superabsorbent hydrogel according to claim 6 in the preparation of a medicament for treating obesity, diabetes, non-alcoholic fatty liver disease or chronic idiopathic constipation.
8. A polymer, characterized in that It is a polysaccharide cross-linked with preformed spacer cross-linkers, wherein the preformed spacer crosslinker comprises a first optionally substituted aliphatic moiety terminated at each end with a second moiety comprising at least two carboxylic acid groups, and wherein the preformed spacer crosslinker is formed by reacting a first optionally substituted aliphatic molecule comprising at least two hydroxyl groups with a second molecule comprising at least three carboxylic acid groups, The first optionally substituted aliphatic moiety is derived from the first an optionally substituted aliphatic molecule, the first optionally substituted aliphatic molecule comprising at least two hydroxyl groups is polyethylene glycol having a molecular weight in the range of 0.1 kDa to 100 kDa; The second moiety comprising at least two carboxylic acid groups is derived from citric acid; and The polysaccharide is selected from sodium carboxymethylcellulose.
Citation Information
Patent Citations
Super-absorbent polymer, super-absorbent gel and preparation method thereof
CN111690156A